2013
DOI: 10.5099/aj130200154
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach for Measurement of Total Reactive Oxidant Species (ROS) In Vivo by A Fluorometric Method

Abstract: Six healthy participants were given a single dose of 100 mg of CoffeeBerry® whole coffee fruit extract containing high levels of antioxidants to verify an acute effect of the treatment on ROS serum level. Blood samples were collected at 0 min, 60 min, 120 min and 180 min for subsequent measurements of serum ROS level using dihydrorhodamine 6G (DHR6G) as a fluorescent probe. The nonfluorescent DHR6G, after being oxidized by ROS present in serum samples, became rhodamine 6G (R6G) and emitted fluorescence. By qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In our previous study, we first demonstrated the use of DHR6G as a fluorometric assay for ROS in vivo (Nemzer et al. ). The theory behind using DHR6G is that nonfluorescent DHR6G will emit fluorescence after being oxidized by ROS.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we first demonstrated the use of DHR6G as a fluorometric assay for ROS in vivo (Nemzer et al. ). The theory behind using DHR6G is that nonfluorescent DHR6G will emit fluorescence after being oxidized by ROS.…”
Section: Introductionmentioning
confidence: 99%